Inhibition of wild‐type p53‐induced phosphatase 1 promotes liver regeneration in mice by direct activation of mammalian target of rapamycin. Issue 6 (25th March 2015) - Zhang, Lingling; Liu, Leiming; He, Zhiyong; Li, Guangbing; Liu, Junping; Song, Zhangfa; Jin, Hongchuan; Rudolph, Karl Lenhard; Yang, Huayu; Mao, Yilei; Zhang, Lianfeng; Zhang, Hongbing; et al.
<x xml:space="preserve">Abstract</x> The liver possesses extraordinary regenerative capacity in response to injury. However, liver regeneration (LR) is often impaired in disease conditions. Wild‐type p53‐induced phosphatase 1 (Wip1) is known as a tumor promoter and enhances cell proliferation, mainly by deactivating antioncogenes. However, in this work, we identified an unexpected role of Wip1 in LR. In contrast to its known role in promoting cell proliferation in extrahepatic tissue, we found that Wip1 suppressed hepatocyte proliferation after partial hepatectomy (PHx). Deletion of Wip1 increased the rate of LR after PHx. Enhanced LR in Wip1‐deficient mice was a result of the activation of the mammalian target of rapamycin (mTOR) complex 1 (mTORC1) pathway. Furthermore, we showed that Wip1 physically interacted with and dephosphorylated mTOR. Interestingly, inhibition of Wip1 also activated the p53 pathway during LR. Disruption of the p53 pathway further enhanced LR in Wip1‐deficient mice. Therefore, inhibition of Wip1 has a dual role in LR, i.e., promoting hepatocyte proliferation through activation of the mTORC1 pathway, meanwhile suppressing LR through activation of the p53 pathway. However, the proregenerative role of mTORC1 overwhelms the antiproliferative role of p53. Furthermore, CCT007093, a Wip1 inhibitor, enhanced LR and increased the survival rate of mice after major hepatectomy. Conclusion: mTOR is a new direct target of Wip1. Wip1 inhibition can activate the mTORC1 pathway and enhance hepatocyte proliferation after hepatectomy. These findings have clinical applications in cases where LR is critical, including acute liver failure, cirrhosis, or small‐for‐size liver transplantations. (Hepatology 2015;61:2030‐2041)